Strategi Dalam Manajemen Pemasaran - Regina Utami Nasution; Nuri Aslami (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2022)
Human life in modern times has various kinds of risks and dangers. Humans as thinking creatures certainly do not know what will happen tomorrow and where they will die. Insurance is a financial means in managing household life, both in facing basic risks such as the risk of death or in dealing with the risk of property in dealing with the risk of the property owned. In the marketing process, it is necessary to implement an essential strategy, the company's main target is in a broad market reach so that a strategy is needed before entering the market, detailing all plans that have been put together, comprehensively and integratedly designed to ensure the company's main objectives can be achieved through the implementation of a segmentation strategy. , and targets at PT Allianz Life Indonesia, as well as knowing whether the marketing strategy implemented is in accordance with the characteristics of sharia marketing. This research uses literature study research. The results of the study indicate that the market segmentation carried out by the Sharia Insurance company Allianz Life Indonesia has grown more rapidly and progressed from year to year. And this makes insurance companies in particular. Keywords: marketing strategy, sharia insurance, PT Allianz Life Indonesia